(untitled) (Far Western Review, 2025)
This study examines the determinants of investment awareness among Generation Y investors in the Nepalese capital market using a mediation-based structural equation Modeling (SEM) framework. A survey of 378 Nepalese investors aged 28-43 years was conducted to assess the influence of financial literacy and saving behavior on investment awareness as well as the mediating role of self-control. The results reveal that financial literacy significantly affects investment awareness, with this effect entirely mediated by self-control (72.32% mediation). Savings behavior demonstrates both a direct and indirect effect on investment awareness, with self-control partially mediating this relationship (53.57% mediation). Although the convergent validity of the investment awareness construct was marginal, the measurement model exhibited strong reliability and discriminate validity. These findings underscore the critical role of self-control in translating financial knowledge and savings habits into investment awareness. The study advocates for comprehensive financial education programs in Nepal that integrate traditional literacy components with training in behavioral self-regulation, particularly targeting predominantly young and inexperienced investor demographics. The insights contribute to the behavioral finance literature by validating social cognitive theory in an emerging market context and offer practical guidance for policymakers aiming to enhance retail investor participation. Future research should explore longitudinal designs and additional psychological factors to further elucidate the complex interplay between financial knowledge, behavior, and investment decision making in developing economies.